Evaluation on the Zn2+ ion adsorption capacity in water of Spirulina platensis biomaterial - Thi Quynh, Hoang; Thi Thuy, Duong; Thi Oanh, Doan; Thi Nhu Huong, Nguyen; Phuong Thu, Le; Mai Lan, Nguyen; Minh Thu, Bui Nguyen; Duc Dien, Nguyen (Vietnam Journal of Biotechnology, 2022)
Due to its rising accumulation in the food chain and ongoing presence in ecosystems, metal contamination has piqued the curiosity of experts from all over the world. Environmentally hazardous heavy metal removal is being pursued utilizing a variety of techniques, such as ion exchange and precipitation, as well as chemical oxidation or reduction, electrochemistry, and filtration. However, these methods require high investment and operating costs, and generate toxic sludge. Spirulina platensis, a filamentous cyanobacteria species, has been reported as a potential bioadsorbent for the removal of some heavy metals from industrial wastewater. In this study, the bioadsorption of Zn2+ ions in an assumed aqueous solution by the dry biomass of S. platensis TH was investigated. The Zn2+ ion adsorption of biomaterials was evaluated under different conditions, including pH, contact time, temperature, and adsorbent mass. The optimal Zn2+ ion removal efficiency reached 90.32 ± 0.29% at Zn2+ ion concentration of 100 mg/L, pH 5.0, a temperature of 26oC, and a dry biomass dose of 1.5 g/L for 90 min. Langmuir and Freundlich’s isothermal models were used to describe the adsorption isotherm of Zn2+ ions on S. platensis TH. Equilibrium data fitted well with the Langmuir model as well as the Freundlich model, with a maximum adsorption capacity of 34.56 mg Zn2+/g S. platensis TH under the reaction conditions of 1.5 g/L biomass dosage, the contact time of 90 min, pH 5.0, at 26oC. Research results have shown that S. platensis TH biomass is an easy, readily available, low-cost adsorbent and has a high bioadsorption capacity. Therefore, it can be treated as a bioadsorbent in the treatment of wastewater containing Zn2+ ions. This process is not only environmentally friendly but also versatile as an alternative to conventional heavy metal treatment methods.